Transformative Learning : Developing Agency, Independence and Promoting a Strong Sense of Self in Teen Mothers. - Cheung, Lilliemay; Kill, Emma; Turley, Janet (Student Success v.11 n.1 p.66-74 https://doi.org/10.5204/ssj.v11i1.1463, 2020)
Adolescents who become pregnant during their secondary education experience a range of challenges that intersect and limit their opportunities to complete schooling and take up university places. One approach to addressing this issue at an Australian regional university is through the Tertiary Preparation Pathway (TPP) which has been delivered within the Supporting Teenagers with Education, Mothering, and Mentoring (STEMM) program, since 2008. The STEMM program offers teen mothers an opportunity to continue or re-engage with education during and beyond pregnancy. Adopting an intersectionality lens, interviews with adolescent mothers identified three key elements underpinning the success of the TPP/STEMM program: recognising the educational aspirations of teen mothers, developing agency and independence and promoting a strong sense of self. This article aims to provide practical implications for educators wishing to establish or develop programs based on this transformative teaching. [Author abstract]